„W lesie słów się zgubiłam” – o ciszy w poezji Antonia Colinasa i Zbigniewa Herberta - Woźniak, Maria Judyta (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2015)
The objective of this comparative article is to present the similarity of poetic concepts of Antonio Colinas and Zbigniew Herbert. The poets did not know each other, there are no traces of mutual influences to be found in their poetic output either, however, they both seemed to be equally connected with the Mediterranean culture. This article concentrates on the meaning of silence in their poetry seen as a necessary supplement to the art of words, hope for saving the sense from ambiguity and hubbub of words. Insufficiency of both the accessible language and silence inspires the poets to seek a form of expression that could satisfy human needs, “the unattainable language.” The search, between the word and silence, is manifested in the poetic works of Colinas and Herbert.